2022
DOI: 10.2147/ijwh.s351795
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Intrapartum Practice and Associated Factors Among Obstetric Care Providers Working in Public Hospitals of South Wollo Zone North-Central Ethiopia: An Institutional-Based Cross-Sectional Study

Abstract: Background Even though recent progress, Ethiopia continues to be one of the most significant contributors to the worldwide burden of maternal mortality. Evidence-based intrapartum practices have significant value to improve the health outcome of the mother and the neonate. However, in Ethiopia, it is not exercised according to the standard. Assessing the proportion of evidence-based intrapartum practice and predictors is essential and vital to providing better-quality care to laboring mothers. Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 22 publications
(27 reference statements)
2
11
5
Order By: Relevance
“…This finding is consistent with a cross-sectional study conducted in Addis Ababa, Ethiopia (24). It is also supported by most recent study conducted in south wollo zone of Ethiopia (23). Another multi-institutional study done in United States also showed that health practitioners who had adequate knowledge was statistically associated with evidence based practice (30).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…This finding is consistent with a cross-sectional study conducted in Addis Ababa, Ethiopia (24). It is also supported by most recent study conducted in south wollo zone of Ethiopia (23). Another multi-institutional study done in United States also showed that health practitioners who had adequate knowledge was statistically associated with evidence based practice (30).…”
Section: Resultssupporting
confidence: 77%
“…The finding revealed that the overall magnitude was 63.7%. This figure is higher than previous studies conducted in Ethiopia, in referral hospitals of Amhara regional state (38.2%) (22), in public hospitals of Addis Ababa (51%) (24) and in public hospitals of South Wollo zone (54.7%) (23). This discrepancy might be due to a difference in the number of hospitals and sample size difference.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations